Implementasi Perlindungan Hukum Petani Tembakau dalam Hukum Indonesia - Aviessita Mar'ah Nuruttamami; Rumawi Rumawi; Udiyo Basuki; ST. Sariroh; Sukron Mazid; Mohammad Ali; Supianto Supianto; Freddy Hidayat; Sholikul Hadi (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This study discusses the legal problems faced by tobacco farmers in Sukorejo Village, Kotaanyar District, Probolinggo Regency due to the closure of large tobacco warehouses that force them to depend on middlemen. This condition causes legal uncertainty, an imbalance in the bargaining position, and alleged violations of the principle of healthy business competition, thus having a direct impact on the economic sustainability of farmers. The focus of this research is to describe the practice of business competition and its impact on tobacco farmers and explain the form of legal protection from the perspective of business competition law and sharia economic law. The research method used is empirical law with a sociology approach to law and legislation, through observations, interviews, and documentation from farmers, middlemen, and factories. The results of the study show that there is dominance of middlemen in cooperation with large factories so that farmers lose freedom in determining prices. This condition does not reflect the principles of fairness and transparency in business competition. Legal protection is still weak because there is no regulation of the basic price or a definite buying and selling mechanism. In the perspective of sharia economic law, the practice violates the principles of al-adl (justice) and al-amanah (honesty). In conclusion, preventive legal protection is needed in the form of price regulation and the establishment of marketing cooperatives, as well as repressive protection through law enforcement against unfair business competition practices.